Development of a Speech-Assistive Device Integrated in an Android Mobile Application for Individuals with Incomplete Locked-In Syndrome - Retona, Alex M (Archīum Ateneo, 2019)
Bridging the communication gap between speech-impaired individuals who are also physically-disabled is essential to maintain their social integration in the society. With this, a speech-assistive device integrated in an Android mobile application was developed. An integrated sensor box was designed to interface five sensors capable of detecting physical movements. These movements are then translated into digitals signals and transmitted to the developed Android mobile application using Bluetooth communication. This allows the user to communicate through the features of the mobile application such as text-to-speech and pictograms using a single-input interface. From here, a case study was conducted on two individuals who both suffered from stroke, inhibiting their speech and physical movements. Their limited but controllable movements such as blinking, and finger gestures were detected. The results also showed the limitation of the system as it requires practice to effectively use the system. As such, the developed speech-assistive system can be a potential form of physical and mental rehabilitation as a learning curve can be developed when using the mobile application. In conclusion, this study demonstrates an accessible and flexible speech-assistive system for disabled individuals to improve their mental health and social relationships with others.